Introduction to Electroweak Baryogenesis - Radouane Gannouji (Galaxies, 2022)
We present a pedagogical introduction to the electroweak baryogenesis. The review focuses principally on the sphaleron and baryon number (non)-conservation or chiral anomaly. All results are derived with details for a self-contained reading.